Biodamage and biodegradation of polymeric materials new frontiers - Pekhtasheva, Elena L.; Neverov, A. N.; Zaikov, Gennady E. (Smithers Rapra, 2012)
Biodamage comprises a wide range of damage by bacteria, fungi, insects and rodents during long-term storage, production, transportation and operation. This research is urgent for ecology and the struggle against environmental contamination. The biodamage problem is both scientifically complex and practically diverse. The first objective of this book is to provide detailed information on three interrelated parts: bacteria and fungi (source of biodamages); insects and rodents (depredators); and materials and products damaged by living organisms. The most modern data on morphology and physiology of biodegrading microorganisms are presented. The second objective is to provide the reader with a systematisation of biological degradation on natural and synthetic materials and products (plastics, textile, fibres, leather and fur, wood and so on). It presents the problem of utilisation of polymeric wastes using microorganisms and main protection methods and technology for raw materials and semiproducts. It also offers practical recommendations in the struggle against biodamage by insects (moth, leather beetles, wood-fretters, cockroaches and termites) and rodents (mice and rats). This volume is intended to be a practical guide on biodamage and biodegradation of polymeric materials, offering a reference to students and researchers from academia and the industry.
Keywords: Polymers -- Biodegradation.; Chemical kinetics.; elektronické knihy; electronic books